Sesbania reduces fertilizer use and increase energy efficiency and profits of rice crop - Rautaray, S K (Indian Farming, 2019)
Agricultural systems face increased problem of food production, especially, in densely populated countries like China, India, Pakistan and Bangladesh. High calorie food crops (rice, wheat, maize and tubers) are extensively grown to meet the energy need of the poor people. Globally, rice, wheat and maize account 42% of calorie intake. Unfortunately, for optimum yield, these crops need high rate of fertilizer application, especially N followed by P and K. These high calorie food crops respond promptly to the application of N. The nutrient element N is universally deficient in soils of hot tropics and subtropics. There is visible improvement in crop greenness, 2 to 3 days after application of N fertilizer. So, the farmers are easily convinced about the benefits of N application. To meet the growing demand of food per unit area, farmers have increased the application of inorganic fertilizers (IF). This has resulted in increased fertilizer production and supply to farmers. In India, the N fertilizer consumption was 18 million tonnes in 2012-13 which was 4.5 times higher than that in 1981-82. India produced 24.5 million tonnes urea (14.7 million tonnes N) in 2015-16 which accounted 82% of total N consumption. Globally, 58% of the increase in N demand between 2014 and 2018 would be from Asia, 22% from America, 11% from Europe, and 8% from Africa. Among the Asian countries, bulk increase in world demand for nitrogen is expected to come from China (18%) and India (17%), followed by Indonesia (6%), Pakistan (4%), Bangladesh (2%) and Vietnam (2%).